Anti-E as a cause of hemolytic disease of the newborn - Cheepsattayakorn R. (2014)
A case of HDN caused by anti-E antibody is reported. A group A, E-positive, hemoglobin E trait female infant was born from a group A, E-negative, beta-thalassemia/hemoglobin E mother. Hyperbilirubinemia was noted at the first day of life. The DAT was positive. Anti-E was detected in the maternal serum. Jaundice and anemia occurring to the baby were severe enough to require phototherapy intervention for 9 days and 50 ml of group A, E-negative packed red blood cells was transfused. The baby's condition improved. She was discharged at 12 days of age. Follow-up of the baby at 1 year old showed that she was alive and in good health.